The cotton and textiles industry : perspectives on industrial maturity and decline - Veit Wilson, John H.; Toms, Steven; Wong, Nicholas D. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This shortform book presents key peer-reviewed research on industrial history. In selecting and contextualising this volume, the editors address how the field of textile history has evolved. Themes covered include entrepreneurial, technological and labour history, whilst the book highlights the strategic and social consequences of innovations in the history of this key UK sector. Of interest to business and economic historians, this shortform book also provides analysis and illustrative case-studies that will be valuable reading across the social sciences"--
Growth, profit and technological choice : the case of the Lancashire cotton textile industry / Steven Toms -- Ring and mule spinning in the nineteenth century : a technological perspective / Roger Holden -- Industrial relations and technical change : profits, wages and costs in the Lancashire cotton industry, 1880-1914 / Stephen Procter and Steven Toms -- Capital ownership, capital structure and capital markets : financial constraints and decline in the Lancashire cotton textile industry, 1880-1965 / David Higgins and Steven Toms -- Quiet successes and loud failures : the UK textile industries in the interwar years / Sue Bowden and David Higgins -- The decline of the UK textile industry : the terminal years 1945-2003 / Allan Ormerod.
OCLC-licensed vendor bibliographic record.
Keywords: Cotton textile industry -- England -- Lancashire -- History; Textile industry -- Great Britain -- History; Textile industry -- England -- History; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Corporate & Business History; BUSINESS & ECONOMICS / Economic History